The role of job embeddedness in new generation migrant workers turnover intention in Guizhou province of China - Tang, MeiRun; Soo, Jennie Hooi Sin; Chuah, Chin Wei (2017)
Nowadays, new generation migrant workers have become the major component of migrant workers in China.As an important part of China’s labor force supply, new generation migrant workers’ high voluntary turnover rates have been widely concerned.Identified by the household registration system and land contract system in China, although migrant workers work in non-agricultural sectors, they still hold rural resident household registration.Due to this different social identity with the urban workers, new generation migrant workers usually face identity discrimination (difference between farmers and urban workers) and are difficult to integrate into their working organization.The rural resident household registration acts as a potentially salient social category with which new generation migrant workers can develop identification in their organizations, by which they identify the congruence of values and goals between individual and the organization that contribute to their work enthusiasm and organizational commitment and later lead to frequently job change.Thus, this study seeks to investigate the relationship between organization identification and turnover intentions in the sample of new generation migrant workers, which is mediated by on-the-job embeddedness.Additionally, this study also tests the moderating effect of off-the-job embeddedness on the relationship between on-the-job embeddedness and turnover intention.